THE ROLE OF PHYSICAL EXERCISES APPLIED THROUGH KINESIOLOGY IN LORDOSIS CORRECTION - Elena Rata; Florian Benedek (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement, 2018)
In the case of this new research we selected and applied the most effective means of correcting the lordosis, physical exercises with the highest degree of correction, as well as the intensity at which these must be made to achieve as rapidly as possible the desired results.Corrective exercises are necessary in the kinesiology recovery and that is why finding the best methods and their application in treating lordosis positively affects the treatment process of this disorder. The treatment period needs such an intervention and obtaining results as favorable during treatment sessions.